PENANGANAN RESERVASI KAMAR MELALUI TELEPON UNTUK TAMU INDIVIDUAL DI BEST WESTERN PREMIER LA GRANDE HOTEL BANDUNG - Imam Ardiansyah (Jurnal Hospitality dan Pariwisata, 2020)
Room reservation must be done carefully to prevent errors because it is very influential when guests come to the hotel to check-in because prospective guests want the request they want by room booking service can be fulfilled, this must be done well because it is very influential on the occupancy rate of the hotel and the hotel. Based on observations made at the Best Western Premier La Grande Bandung Hotel, there are several issues related to the Standard Operational Procedure for handling individual guest room reservations so that it can have an impact on guest satisfaction. Descriptive research method is research conducted to determine the value of a variable or more without making comparisons or connecting one variable to another variable. This research was conducted in April - June 2015. Based on the final results of the analysis of the questionnaire study, it was handled the telephone room reservation at the Best Western Premier La Grande Bandung Hotel from the aspect of Standard Operating Procedures resulting in 239 points in the "Performed" category, while Equipment and Media produced points as many as 77 are included in the category "Enough" and for Employee Competency to produce as many as 158 points and fall into the category "Agree